Measurement of Impact of Banking System Development on Economic Growth in Iraq - خلف, عمار حمد (Journal of Economics and Administrative Sciences, 2011)
At the heart of every robust economy is a vital banking system. The functional banking system can effectively perform several functions such as mobilizing savings, allocating credit, monitoring managers, transforming risks, and facilitating the financial transactions. This paper aims to measure the impact of banking system development on economic growth in Iraq. Credit to private sector divided by GDP used as a proxy of banking development. Real per capita GDP used as a proxy of economic growth. By using Autoregressive Distributed Lag (ARDL) model, the paper finds that the undeveloped Iraqi banking system could not promote economic growth in the country. Therefore, a variety of policies need to be taken to spur the role of banking system in overall process of economic development in Iraq. For instance; encouragement of private sector in the economy, reducing the role of informal activities of private sector into economy, eliminating the policies of financial repression, and more importantly, set up the political and security stability.The paper divided into the following sections: 1) introduction, 2) literature review, 3) development of Iraqi banking system, 4) econometric model, 5) analysis of the results, and 6) findings.